Rancang Bangun Aplikasi Emergency Call Berbasis Hybrid Mobile - Khairul Fadhly; Nizirwan Anwar (Prosiding SISFOTEK, 2023)
Everyday life exposes us to a variety of dangerous situations that pose a threat to ourselves or others, such as robberies, accidents, etc. In this situation, we need immediate assistance. In 2013, the Tangerang Regency itself had a crime rate of 3,109, according to the Tangerang Regency Central Statistics Agency. Based on the high crime rate, the purpose of this research is to develop a Hybrid-based application system that can be accessed via Android and the website so that residents of the Tangerang district can call public service numbers and important Emergency numbers to receive assistance in the event of a crime or accident. It is anticipated that this Hybrid application will make it easier for users to contact Emergency services in the event of a crime or accident. It will be discussed how to utilize this application for Emergency needs utilizing Location-Based Services (LBS) and simple access to required public service contacts. This study aims to design and develop an application for a Hybrid-based LBS-based IONIC-based Emergency notification system for the Tangerang district